1994
DOI: 10.1007/bf00302251
|View full text |Cite
|
Sign up to set email alerts
|

Transposon mutagenesis of coryneform bacteria

Abstract: The Corynebacterium glutamicum insertion sequence IS31831 was used to construct two artificial transposons: Tn31831 and miniTn31831. The transposition vectors were based on a gram-negative replication origin and do not replicate in coryneform bacteria. Strain Brevibacterium flavum MJ233C was mutagenized by miniTn31831 at an efficiency of 4.3 x 10(4) mutants per microgram DNA. Transposon insertions occurred at different locations on the chromosome and produced a variety of mutants. Auxotrophs could be recovered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
27
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 20 publications
2
27
1
Order By: Relevance
“…However, both ends of the 8-nt target duplication are rich in GC with an AT-rich central region, for example, TCATTG CCC (endogenous copy), GCCAAAAC (mutant A1), and AC GAAAGT (mutant A27). For the transposons derived from IS1096 and IS31831 (18,37), the same pattern was reported for the insertion sites. This may often lead to insertions within promoter regions in these high-GC gram-positive bacteria; for example, this may have occurred in mutant A27.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…However, both ends of the 8-nt target duplication are rich in GC with an AT-rich central region, for example, TCATTG CCC (endogenous copy), GCCAAAAC (mutant A1), and AC GAAAGT (mutant A27). For the transposons derived from IS1096 and IS31831 (18,37), the same pattern was reported for the insertion sites. This may often lead to insertions within promoter regions in these high-GC gram-positive bacteria; for example, this may have occurred in mutant A27.…”
Section: Discussionsupporting
confidence: 63%
“…The transposition rates of about 10 3 transpositions/g of DNA used in electroporation of Arthrobacter are in the same range as those obtained with transposons constructed from IS1096 (3) and IS31831 (37). Since transposition rates strictly depend on the efficiency of transformation, transposon mutagenesis requires optimization of the conditions for electroporation.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…IS31831 exhibits cointegrate formation and resolution (47) and IS1096 was shown to contain a putative resolvase (12). It was suggested that IS1411 might transpose via circle formation (23), as has been shown to occur during the transfer of conjugative plasmids (37).…”
Section: Discussionmentioning
confidence: 99%
“…Information is emerging about the existence of such mobile elements (insertion sequence [IS] elements or transposons) in corynebacteria. Vertès et al (41) described the presence in Corynebacterium glutamicum of the element IS31831 and used it to construct two artificial transposons (Tn31831 and miniTn31831) which were functional in a Brevibacterium flavum strain (39). A new IS element (IS1206) from C. glutamicum has been described by Bonamy et al (5), and a different one (IS13869) has been isolated from Brevibacterium lactofermentum (7).…”
mentioning
confidence: 99%